From Garden to School Treasury: The Strategic Role of Public Relations in Optimizing Kindergarten Hydroponic Programs - Amanatul Uluwiyah; Yudithia Dian Putra; Imron Arifin (Managere: Indonesian Journal of Educational Management, 2025)
This study investigates the strategic role of public relations (PR) management in optimizing hydroponic programs at the kindergarten level. Employing a qualitative descriptive case study design, data were collected through interviews, direct observation, and document analysis, validated using triangulation and member checking. The findings reveal four critical themes: innovation-based program planning with financial independence, structured team organization and role allocation, effective communication and stakeholder engagement, and continuous supervision and evaluation. Collectively, these themes demonstrate how PR transforms hydroponic initiatives from extracurricular activities into sustainable, income-generating school business units. Specifically, PR fosters innovation through creative product processing, enhances credibility via transparent communication, and strengthens institutional resilience through systematic monitoring. This study highlights the novelty of integrating entrepreneurial principles into early childhood education through PR, offering a practical model for schools seeking economic empowerment. The implications highlight the importance of proactive PR as a catalyst for sustainable school programs, enriching educational management literature by linking communication strategies, entrepreneurial practices, and community involvement.